Designing of Electronic Employee Recruitment System Using The Analytical Hierarchy Process Method - Sidrotun Naim; Sarwo Hakim; Samuel PD Anantadjaya; Irma M. Nawangwulan; Zulkifli (Jurnal Sistim Informasi dan Teknologi, 2023)
A computer-based information system called the Decision Support System (DSS) generates several decision alternatives to help management cope with diverse issues in a semi-structured way. As a company engaged in marine survey services, the process of hiring new employees is important. It takes a long time to choose and decide whether to accept potential employees under the present recruitment procedure, and HRD is having trouble making decisions on accepting applicants who satisfy the requirements. Building a decision-support system for employing people is the aim of this research. The Rapid Application Development (RAD) model is the system development approach used in this study. The Unified Modelling Language (UML) is used in the system design. System coding is done using PHP and MySQL. The results of the AHP method are applicants who have the highest criterion value, meaning that they have a higher value than other applicants, so that companies can get the employees they want according to the criteria specified in the form of tables and rankings. The manager can get help from this decision-support system when making a choice.